Sudan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Sudan during 1990-94. In 1993 and 1994, the authorities decided to redress the economic imbalances by adopting a more comprehensive approach aimed at substantially lowering the rate of inflation through tighter fiscal and monetary restraint along with a more flexible exchange rate policy. Government expenditure was contained more tightly, particularly through cuts in investment outlays: the primary deficit and government recourse to domestic bank financing fell significantly in 1993/94. However, the fiscal and monetary policies put in place failed to lower inflation below 100 percent in 1992/93 and 1993/94.